Referring to God : Jewish and Christian Perspectives. - Helm, Paul (Routledge Jewish studies series., 2013)
There is a long tradition of discussion in the philosophy of religion about the problems and possibilities involved in talking about God. This book presents accounts of the problem within Jewish and Christian philosophy.